Ideology of Gogirl Magazine Through Representation of Youth Women in Magazine Cover". Critical Analysis Of Young Womens Representation In West Celebrity Photo On Gogirl Cover Magazine - Tajisalli Nur Sabarrang (KOM & REALITAS SOSIAL, 2011)
This study aims to analyze the ideology of the Gogirl magazine through the representation of women in the covers of Gogirl magazines Â by seeing (1) the meaning of denotation of west celebrity images / photos on the Gogirl cover magazine (2) the meaning of the connotation of west celebrity images / photos on Gogirl cover magazine (3) the myth of west celebrity images / photos on Gogirl cober magazine (4) ideological values of west celebrity Â image / photo on the Gogirl cover magazine of celebrity magazines Gogirl west, (5) market ideology taken Gogirl magazine. As this research used a subjective approach, with qualitative research methods through the critical analysis of Jurgen Habermas and semiotic analysis of Roland Barthes. Research results indicate that (1) The meaning of denotation of the western celebrity photo is A young woman "Caucasians" white-skinned clean, sharp nose, colored haired blondie, posing with the girly hair and natural makeup. (2) meaning the connotation of the western celebrity photo is west Celebrity / Hollywood actress aesthetically beautiful with makeup that matches the girls. He is posing with a trendy clothes and stylish for wearing clothing that is up to date. implies a pure and innocent, strong and independent as well as elegant. (3) the myth of the use of celebrity photographs are western beauty myth, myth fashionable, and the myth of success. (4) ideological values contained in the images / photos is femininity. (5) The ideology of the market taken by the Gogirl magazine adopters of womens magazines are publications that circulate in western Indonesia on the basis of market interest.